Alcohol use in the first three years of bereavement: a national representative survey - Pilling János; Konkolÿ Thege Barna; Demetrovics Zsolt; Kopp Mária S (BMC, 2012)
Abstract Background Earlier results concerning alcohol consumption of bereaved persons are contradictory. The aim of the present study was to analyze the relationship between bereavement and alcohol consumption accounting for time and gender differences on a nationally representative sample from Hungary ("Hungarostudy Epidemiological Panel Survey", N = 4457) Methods Drinking characteristics of mourning persons (alcohol consumption, dependence symptoms, and harmful consequences of alcohol use) in the first three years of grief were examined among persons between 18-75 years using the Alcohol Use Disorders Identification Test (AUDIT). Results Men bereaved for one year scored higher on two dimensions of AUDIT (dependence symptoms and harmful alcohol use), while men bereaved for two years scored higher on all three dimensions of AUDIT compared to the non-bereaved. The rate of men clinically at-risk concerning alcohol consumption among the non-bereaved is 12.9%, and among men bereaved for one year is 18.4% (a non-significant difference), while 29.8% (p < 0.001, OR = 2,781) among men bereaved for two years. However, men bereaved for three years did not differ from the non-bereaved in their drinking habits. In case of bereaved women, again no difference was found with respect to alcohol use compared to the non-bereaved. Conclusion Among bereaved men, the risk of alcohol related problems tends to be higher, which can be shown both among men bereaved for one year as well as men bereaved for two years. Considering the higher morbidity and mortality rates of bereaved men, alcohol consumption might play a mediator role. These facts draw attention to the importance of prevention, early recognition, and effective therapy of hazardous drinking in bereaved men.